2001
DOI: 10.1677/joe.0.1700333
|View full text |Cite
|
Sign up to set email alerts
|

The role of the IGF axis in IGFBP-1 and IGF-I induced renal enlargement in Snell dwarf mice

Abstract: Insulin-like growth factor (IGF) binding protein-1 (IGFBP-1) is generally believed to inhibit IGF action in the circulation. In contrast, IGFBP-1 has been reported to interact with cell surfaces and enhance IGF-I action locally in some tissues. Renal IGFBP-1 levels are found elevated in various conditions characterized by renal growth (e.g. diabetes mellitus, hypokalemia).To test whether IGFBP-1 is a renotropic factor, IGFBP-1 was administered alone or in combination with IGF-I to Snell dwarf mice, an in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…IGFBP-6 mRNA is weakly expressed in the mouse kidney, being undetectable in the adult kidney. Similar expression pattern of IGF system mRNA, mostly co-localizing with its protein, was observed in kidney of adult Snell dwarf mice [31]. Northern blot analysis revealed abundant expression of IGFBP-1 to -5, while IGFBP-6 could not be detected in the adult mouse kidney [8,19,21].…”
Section: Expression Of Gh/igf System In the Rodent Kidneysupporting
confidence: 60%
“…IGFBP-6 mRNA is weakly expressed in the mouse kidney, being undetectable in the adult kidney. Similar expression pattern of IGF system mRNA, mostly co-localizing with its protein, was observed in kidney of adult Snell dwarf mice [31]. Northern blot analysis revealed abundant expression of IGFBP-1 to -5, while IGFBP-6 could not be detected in the adult mouse kidney [8,19,21].…”
Section: Expression Of Gh/igf System In the Rodent Kidneysupporting
confidence: 60%
“…Thus SGK1 could participate in the regulation of kidney growth and glomerular permeability. SGK1 is activated by IGF-I, a hormone implicated in the regulation of cell proliferation and renal growth (4,13,16,17,23,25,38,55,60). Moreover, excessive SGK1 transcription has been observed in diabetic nephropathy (31,32) and glomerulonephritis (15).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBPs have also been implicated in the development of nephropathy in human and rodent models (3,4,(23)(24)(25)(26)30,32,33). Flyvbjerg et al (33) and Landau et al (31) reported that the growth hormone, the principle biological regulator of IGF-I secretion, enhances diabetes-related renal IGFBP-1 upregulation at the mRNA and protein levels and exacerbates diabetic renal hypertrophy in STZ rats.…”
Section: Igfbp-1 Snps and Diabetic Nephropathymentioning
confidence: 99%
“…Renal hypertrophy is an earlyonset feature of experimental diabetic nephropathy and is correlated with an increase in IGF-I and a transient spike in IGFBP-1. However, cortical regulation of the IGF effect is mediated by IGFBPs (3,4,[23][24][25][26][27]. Feldmann et al (27) reported lower free IGF-I levels but an elevated total IGF-1 level, strongly suggesting a modulatory role for IGFBPs in this process.…”
mentioning
confidence: 99%